2013
DOI: 10.1097/01.aud.0000436255.53747.a4
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Automated Threshold Audiometry

Abstract: Automated audiometry provides an accurate measure of hearing threshold, but validation data are still limited for (1) automated bone conduction audiometry; (2) automated audiometry in children and difficult-to-test populations and; (3) different types and degrees of hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…Mahomed et al (2013) provides a detailed systematic review and meta-analysis of the literature comparing automated pure-tone air-conduction threshold audiometry with the gold standard of manual threshold audiometry. The researchers conclude that automated audiometry provides an accurate measure of hearing threshold using air-conducted pure-tones as stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Mahomed et al (2013) provides a detailed systematic review and meta-analysis of the literature comparing automated pure-tone air-conduction threshold audiometry with the gold standard of manual threshold audiometry. The researchers conclude that automated audiometry provides an accurate measure of hearing threshold using air-conducted pure-tones as stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…A series of validation studies demonstrated that the method produces thresholds with average values that are equivalent to those obtained by experienced audiologists (Margolis et al 2010; Margolis & Moore 2011; Margolis et al 2011). An independent assessment of AMTAS (Eikelboom et al 2013) replicated the finding of equivalence between AMTAS and manual audiometry and a meta-analysis showed good agreement between mean values obtained with automated and manual test procedures (Mahomed et al 2013). AMTAS employs masking based on rules that are consistent with those used in manual audiometry.…”
Section: Audiometric Methodsmentioning
confidence: 73%
“…The threshold of the lowest level was defined when the participants responded to 50% of the pure tone. The reliability and validity of the automated hearing test was good, as compared to the manual test 1112). When the subjects heard the tone, they were instructed to push a button.…”
Section: Methodsmentioning
confidence: 96%